Enjoyment, anxiety, and out-of-class foreign language use among Spanish foreign language learners - Acosta-Manzano, Irene; Barrios-Espinosa, María Elvira; García-Mata, Jorge (Taylor & Francis, 2023)
This study investigated the relationship between Foreign Language Enjoyment (FLE), Foreign Language Classroom Anxiety (FLCA), Out-of-Class Foreign Language Use (OCFLU) and learner factors (FL and FL proficiency level). Participants were 611 foreign language (FL) learners aged 16–72 at Spanish Official Language Schools. An online questionnaire was used to collect the study data. Results revealed that the informants scored high in FLE, moderately in FLCA and quite low in OCFLU; FLE was positively related to OCFLU, while FLCA was negatively associated with it; these two associations held in FL proficiency levels below higher-intermediate (B2) for all foreign languages considered. This study confirms previous research, adds new evidence concerning the relationship between FLE and FLCA and OCFLU, and considers the implications for FL teaching and learning in formal situations, with particular attention to autonomous learning in an increasingly digitalised world.
Keywords: Segunda lengua - Adquisición; Foreign Language Classroom Anxiety; Foreign language enjoyment